Thermal relics in modified cosmologies: bounds on evolution histories of the early Universe and cosmological boosts for PAMELA - Catena, Riccardo; Fornengo, N.; Pato, M.; Pieri, L.; Masiero, A. (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
Alternative cosmologies, based on extensions of general relativity, predict modified thermal histories in the early Universe during the pre-big bang nucleosynthesis era, an epoch which is not directly constrained by cosmological observations. When the expansion rate is enhanced with respect to the standard case, thermal relics typically decouple with larger relic abundances. The correct value of the relic abundance is therefore obtained for larger annihilation cross sections, as compared to standard cosmology. A direct consequence is that indirect detection rates are enhanced. Extending previous analyses of ours, we derive updated astrophysical bounds on the dark matter annihilation cross sections and use them to constrain alternative cosmologies in the pre-big bang nucleosynthesis era. We also determine the characteristics of these alternative cosmologies in order to provide the correct value of relic abundance for a thermal relic for the (large) annihilation cross section required to explain the PAMELA results on the positron fraction, therefore providing a “cosmological boost” solution to the dark matter interpretation of the PAMELA data.
Gesehen am 26.01.2023